The Moderating Role of Knowledge Management on the Relationship between Employees' Commitment and Total Quality Management: A Study on the Public Healthcare Sector in Saudi Arabia - Al Ghamdi, Abdulrahman Ahmad; Abd. Aziz, Fadzli Shah bin; Yusoff, Rushami Zien; Mustafa, Munauwar bin (International Review of Management and Marketing, 2016)
This current study investigated the relationship between Employees' Commitment and total quality management in the public healthcare sector of Saudi Arabia. Furthermore moderating effect of knowledge management on the relationship between employees' commitment and total quality management has been examined. The core of the paper showed the effectiveness of public health sectors employee's commitment to improve the total quality management. Quantitative methodology for data analyses were employed to test the hypothesized model. A total of 259 questionnaires were distributed among the respondents, out of which 165 questionnaires were returned and only 154 were found useful in sense of completeness and usefulness for further analysis. The results of the analyses confirmed that there is significant direct effect of employees' commitment to improve the total quality management and knowledge management moderates the relationship between employees' commitment and total quality management. Keywords: total quality management, Employees' Commitment, knowledge management, Partial Least Squares, public healthcare JEL Classifications: M1, M12